determine the equation of the circle graphed below
![determine the equation of the circle graphed below class=](https://us-static.z-dn.net/files/d37/c5a3fc36bd7427f6221a8238004f736a.png)
Answer:
The equation would be (x – 3)^2 + (y – 4)^2 = √26^2 or 26.
Step-by-step explanation:
Firstly, we need to find the radius of the circle. In this case, through the Pythagorean theorem, we can find it to be √(9-4)^2 + (4-3)^2 = √25 + 1 = √26.
Therefore, the equation of the circle would be (x – h)^2+ (y – k)^2 = r^2, where h and k are the x and y-coordinates of the center of the circle respectively, and r is the radius. Hence, the equation of this circle would be (x – 3)^2 + (y – 4)^2 = √26^2 or 26.
Hope this helped!
Answer:
Step-by-step explanation:
Equation in standard form:
where (h, k) is the center and r- radius
On the graph we have (h, k) = (3, 4)
Find the r² using the distance formula:
The equation is: